Ruby Rich interviewed by Hazel de Berg in the Hazel de Berg collection - Rich, Ruby, 1888-1988.; De Berg, Hazel, 1913-1984. (1976)
Rich speaks of the beginnings of the Racial Hygiene Association (1926); she explains the objectives of the organisation; the attitude of Government and society towards birth control; she speaks of Viola Smith and her accomplishments as a lawyer; her background and work at the United Nations.
Recorded on Dec. 12, 1976 & May 11, 1977.
Also available online
Timed summary (10 p.) and transcript available (47 leaves)
Keywords: Rich, Ruby -- Friends and associates; Rich, Ruby -- Political and social views; Rich, Ruby, -- 1888-1988. -- Interviews; Racial Hygiene Association of New South Wales